Risk assessment of non-communicable diseases (NCDs) in rural Maharashtra, India (UCC Student Medical Journal, 2024)
The research question I addressed was - “To what extent do socioeconomic factors influence the risk of developing lifestyle diseases such as Obesity, Hypertension and Type II Diabetes Mellitus in Rural and Urban Indian women aged 35-55 years?”.  Having lived in the urban parts of India for the majority of my life, this opportunity exposed me to healthcare in rural India and language barriers due to the diversity of subIndian cultures.
Keywords: non-communicable diseases; NCDs; risk assessment